Tetrameric INTS6-SOSS1 complex facilitates DNA:RNA hybrid autoregulation at double-strand breaks - Long, Qilin; Ajit, Kamal; Sedova, Katerina; Haluza, Vojtech; Stefl, Richard; Dokaneheifard, Sadat; Beckedorff, Felipe; Valencia, Monica G; Sebesta, Marek; Shiekhattar, Ramin; Gullerova, Monika (Nucleic acids research, 2024)
DNA double-strand breaks (DSBs) represent a lethal form of DNA damage that can trigger cell death or initiate oncogenesis. The activity of RNA polymerase II (RNAPII) at the break site is required for efficient DSB repair. However, the regulatory mechanisms governing the transcription cycle at DSBs are not well understood. Here, we show that Integrator complex subunit 6 (INTS6) associates with the heterotrimeric sensor of ssDNA (SOSS1) complex (comprising INTS3, INIP and hSSB1) to form the tetrameric SOSS1 complex. INTS6 binds to DNA:RNA hybrids and promotes Protein Phosphatase 2A (PP2A) recruitment to DSBs, facilitating the dephosphorylation of RNAPII. Furthermore, INTS6 prevents the accumulation of damage-associated RNA transcripts (DARTs) and the stabilization of DNA:RNA hybrids at DSB sites. INTS6 interacts with and promotes the recruitment of senataxin (SETX) to DSBs, facilitating the resolution of DNA:RNA hybrids/R-loops. Our results underscore the significance of the tetrameric SOSS1 complex in the autoregulation of DNA:RNA hybrids and efficient DNA repair.
Keywords: Phosphorylation; RNA Polymerase II; DNA Helicases; DNA-Binding Proteins; Humans; RNA; DNA Breaks, Double-Stranded; R-Loop Structures; DNA vazebné proteiny; dvouřetězcové zlomy DNA; fosforylace; oprava DNA; proteinfosfatasa 2; Protein Phosphatase 2; lidé; DNA-helikasy; RNA Helicases; DNA Repair; DNA; R-smyčka; RNA-polymerasa II; homeostáza; Homeostasis; RNA-helikasy